Epidemiological analysis of syphilis in pregnant women living in Curitiba/PR, Brazil: an observational descriptive study (Brazilian Journal of Health Research, 2021)
Introduction: Syphilis is a curable systemic disease distributed worldwide. Contamination can take place through sexual intercourse, as well as through vertical or blood-borne transmission. Syphilis in pregnant women is a mandatory notifiable disease in Brazil. The aim of the current study is to describe the epidemiology of confirmed syphilis cases in Curitiba City/PR. Methods: Documental-based observational descriptive study. Data were provided by the municipal health department through access to the SINAM database. The period between 2007 and 2017 was taken into consideration for analysis purposes. The following variables were analyzed: age, race, gestational age, schooling, clinical classification, prescribed treatment, and treatment application to sexual partner. The 2018 Syphilis Epidemiological Bulletin was used as counterpoint for the Brazilian average. Results: Based on the analysis applied to the historical series in Curitiba, there was increase in the number of notified cases per year, mainly in 20-29-year-old pregnant women, with incomplete elementary school. The disease was mostly diagnosed at late latent clinical stage and treatment was applied at early pregnancy stages. Most cases in Brazil comprise primary syphilis (32%) with late treatment. Conclusion: Municipal and national data have shown progressive increase in the incidence and prevalence of syphilis in pregnant women. Inaccurate filing of SINAN forms was identified, and it acted as limiting factor in the current study. Thus it is fundamental optimizing the collection of high-quality and easy-access official data to help mitigating this public health issue.
Keywords: Syphilis; Pregnant Women; High Risk Pregnancy; Health Information Systems; Public Health